Areas of endemism of small mammals are underprotected in the Atlantic Forest - Dalapicolla, Jeronymo; Abreu, Edson Fiedler; Do Prado, Joyce Rodrigues; De Almeida Chiquito, Elisandra; De Oliveira Roth, Paulo Ricardo; De Góes Brennand, Pamella Gusmão; Pavan, Ana Carolina D'Oliveira; Pereira, Alex; Mendes, Fabiana Rocha; Del Valle Alvarez, Martin Roberto; Rios, Élson Oliveira; Cassano, Camila Righetto; et al. (Oxford University Press (OUP), 2021)
Atlantic Forest (AF) is amongst the most threatened forests in the world. To decide where conservation efforts should be focused to preserve species, assessment of ecological and biogeographic processes nowadays are crucial. Patterns of the distribution of organisms can provide an important source of information underlying the biogeographical history of a biota. Here, our main objective was to identify Areas of Endemism (AoE) for non-volant small mammals in the AF and to investigate if those AoE are covered by protected areas. We performed quantitative and qualitative approaches to delimit AoE and calculated the area overlaid by Conservation Units (CU) within each AoE. Our results supported the recognition of seven AoE for small mammals in the AF, which largely are congruent with previous studies undertaken on other organisms, thereby highlighting the importance of those regions as hotspots of endemism. Most of the AoE recovered in the present study have less than 12% of their territory covered by forest remnants, and less than 11% of their entire range is under legal protection. These findings bring to light an important discussion on how information pertaining to the representativeness of CU within regions of high endemicity could help to identify areas in need of urgent protection within a threatened biodiversity hotspot.
Keywords: biogeographic patterns; conservation units; Didelphimorphia; distribution; endemicity; Neotropical region; Rodentia; South America; species richness